Cutting-edge potatoes for Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Born again, sweet potato plants developed by a team of local scientists employed by Zimbabwe company Agri-Biotech are helping small-scale farmers in Zimbabwe to weather the country s food crisis...